2009
DOI: 10.1016/j.visres.2009.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning with Chevrons requires a minimal number of trials, transfers to untrained directions, but does not require sleep

Abstract: In most models of perceptual learning, the amount of improvement of performance does not depend on the regime of stimulus presentations, but only on the sheer number of trials. Here, we kept the number of stimulus presentations constant while varying the number of trials per session. We show that a minimal number of stimulus presentations per session is necessary, transfer depends strongly on the presentation regime, but sleep has only weak, if at all, effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 55 publications
7
75
4
Order By: Relevance
“…For both auditory and visual fine-grained discrimination tasks, there is evidence that improvement across days requires sufficient (and sometimes extensive) training per day (Aberg et al, 2009;Wright and Sabin, 2007;Wright et al, 2010), and that additional daily training beyond the sufficient amount provides no further benefit (Aberg et al, 2009;Hauptmann and Karni, 2002;Hauptmann et al, 2005;Wright and Sabin, 2007). In combination, these results suggest that the consolidation of perceptual learning may function as an all-or-none process, a characteristic that could be exploited to help optimize perceptual training regimens (Wright and Sabin, 2007).…”
Section: B Learning Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…For both auditory and visual fine-grained discrimination tasks, there is evidence that improvement across days requires sufficient (and sometimes extensive) training per day (Aberg et al, 2009;Wright and Sabin, 2007;Wright et al, 2010), and that additional daily training beyond the sufficient amount provides no further benefit (Aberg et al, 2009;Hauptmann and Karni, 2002;Hauptmann et al, 2005;Wright and Sabin, 2007). In combination, these results suggest that the consolidation of perceptual learning may function as an all-or-none process, a characteristic that could be exploited to help optimize perceptual training regimens (Wright and Sabin, 2007).…”
Section: B Learning Frameworkmentioning
confidence: 99%
“…Second, perceptual learning appears to require sufficient practice per day, but no more than that. The retention of learning across days requires an adequate number of daily training trials (Aberg et al, 2009;Wright and Sabin, 2007;Wright et al, 2010). Critically, once this number is reached, additional training seems to be superfluous (Aberg et al, 2009;Hauptmann and Karni, 2002;Hauptmann et al, 2005;Ofen-Noy et al, 2003;Ortiz and Wright, 2010;Wright and Sabin, 2007).…”
mentioning
confidence: 99%
“…In many PL models, the stimulus-specificity of PL is attributed to the primary visual cortex (i.e., area V1) where neurons are highly selective for stimulus location and orientation (e.g., Adini, Sagi, & Tsodyks, 2002;Teich & Qian, 2010;Zhaoping, Herzog, & Dayan, 2003). However, some studies found such behavioral stimulus specificity can be eliminated under certain conditions, showing strong transfer of PL effects (Aberg, Tartaglia, & Herzog, 2009;Ahissar & Hochstein, 1997;Harris, Gliksberg, & Sagi, 2012;Hussain, Bennett, & Sekuler, 2012;Liu & Weinshall, 2000;Tartaglia et al, 2009;Xiao et al, 2008). Moreover, some behavioral studies showed task-specificity of PL in which the PL effect cannot transfer from the trained task to another task involving the same or similar stimuli (Ahissar & Hochstein, 1993;Huang et al, 2007;Shiu & Pashler, 1992), though others found successful transfer of learning across tasks (Chung, Legge, & Cheung, 2004;Green & Bavelier, 2003;Leonards et al, 2002;Nazir et al, 2004;Yu, Klein, & Levi, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, have not observed interactions between sleep and perceptual learning (Aberg, Tartaglia, & Herzog, 2009;Hussain, Sekuler, & Bennett, 2009), leaving the role of sleep in learning an open question. In light of these findings, we recorded actigraphic and self-reported measures of sleep throughout the study period to assess the relationship between sleep and sensorimotor performance on the Sensory Station tasks.…”
Section: Sleep Measuresmentioning
confidence: 98%
“…Studies addressing learning in a number of domains including sensory discrimination (Karni et al, 1994;Stickgold, James, & Hobson, 2000), motor skills (Walker et al, 2002), and more general procedural-based skills (Peigneux, Laureys, Delbeuck, & Maquet, 2001) have shown that sleep leads to greater improvements in performance, relative to the same period of wakefulness. Nonetheless, other studies have indicated that sleep may not be important for types of sensory and perceptual learning or may only occur once the perceptual system has been properly adapted to the stimuli (Aberg et al, 2009;Hussain et al, 2009), creating an open question as to the role of sleep in the learning of different skills.…”
Section: Sleep Psychomotor Performance and Learningmentioning
confidence: 99%